ASSESSMENT AND PROSPECTS OF THE DEVELOPMENT OF THE LIFT ECONOMY OF UKRAINE (Transport systems and technologies, 2021)
The article assesses the current state of the city elevator industry, analyzes statistical data that reflect the number of overtime workers in accordance with the established norms of time norms of safe operation and non-working elevators. A comparative analysis of the characteristics of typical elevator drives. It is noted that on the basis of the study it is possible to draw the following conclusions and provide recommendations. In the conditions of budget deficit the organizations servicing elevators need to try to find means for updating or modernization of this type of transport independently that will lead to growth of acceleration of terms of performance of technical works. For example, private investment can be such a source of funding. In the absence of sufficient funding, service organizations can lease the necessary equipment. An important issue is to increase the level of training for quality maintenance of elevators. It is necessary to gradually replace elevators that have served their standard service life (first of all, these are elevators that have worked for more than 35 years, then 25 years, and so on). The renewed elevators should be based on modern innovative technologies that would ensure energy savings and be equipped with the latest methods of control, monitoring the technical condition of the elevator system remotely, it will significantly increase the level of quality and speed of service.
Keywords: elevator electric drive, technical condition of elevator economy, energy saving, frequency converter.